Intraoperative surgeon probe inspection compared to leak testing for detecting gaps in canine jejunal continuous anastomoses: A cadaveric study. Issue 7 (10th August 2021) - Culbertson, Tricia F.; Smeak, Daniel D.; Pogue, Joanna M.; Vitt, Molly A.; Downey, Amy C.
Abstract: Objective: To compare the detection of gaps in jejunal continuous anastomoses by probing (PT) versus leak testing (LT). Study Design: Experimental study. Animals: Normal jejunal segments (n = 24) from two fresh canine cadavers. Methods: Intestinal segments were randomly selected by four volunteers who created six simple continuous anastomoses: two constructs using standard technique with 2–3 mm suture spacing (ST, 8 total), and four constructs with one 4‐mm gap (IG, 16 total). All 24 anastomoses were examined with PT (1 volunteer) prior to LT (3 volunteers). LT was performed within a maximal peristaltic pressure range (34–54 cmH2 O). The presence and location of anastomotic leaks (LA ) detected with LT were compared with gaps detected with PT. Results: Nineteen out of twenty‐four (79.2%) samples had at least one probe drop, and four out of twenty‐three (17.4%) samples leaked. LT results from one sample were excluded due to iatrogenic suture failure. PT was 100% sensitive (95% CI: 51.01, 100%) with a 100% negative predictive value (95% CI: 56.55, 100%) at detecting gaps compared with LT. The location of all LA was accurately identified with PT and confirmed during LT. Conclusion: PT was highly sensitive at detecting gaps compared with LT. All LA were accurately detected by PT. None of the segments negative during PT leaked. Clinical Significance: The diagnostic value of PT appears adequate to recognize gaps in cadaveric small intestinal anastomoses. PT offers surgeons an alternative to detect suture gaps that may contribute to postoperative dehiscence of intestinal anastomoses.